Pengawasan Kepala Dinas Bina Marga dan Bina Konstruksi Provinsi Lampung Dalam Melakukan Kegiatan Rutin Perawatan Jalan Kota Bandar Lampung di Era Covid-19 - M Ajie SetyaJ; Ida Faridah (Jurnal STIA Bengkulu, 2022)
This study aims to find out how the supervision carried out by the head of the Department of Highways and Construction of Lampung Province in carrying out  routine road maintenance activities in the city of Bandar Lampung in the Covid 19 era. This research uses a qualitative research type with descriptive research methods. The theory used is supervision. From the results obtained, routine road  maintenance activities are still prioritized to be carried out in order to create good infrastructure for road users. However, there has been a decrease in the number of workers due to the Covid-19 condition. The inhibiting factors in supervising routine road maintenance activities are field conditions such as road access that is difficult to take for road supervision and repair, local communities who are less concerned with the rules applied during work, and Non Governmental Organizations (NGOs) who often carry out job intimidation. However, on the other hand there are also supporting factors in supervising routine road maintenance activities such as the budget provided by the government has started to return to normal and is sufficient, adequate human resources (HR), the health of staff who routinely checks the health of each employee before the process. working hours, and road conditions that should be regularly maintained.